Vaccination: is it all good? - Aziz, Jazli; Rahman, Mohammad Tariqur (2010)
Vaccination has been practiced for hundreds of years, dating back to the 17th century. Throughout history, the mechanisms of vaccination have been studied, refined and improved into what we know vaccination to be today. However, the overall effect of vaccination may have on the homeostasis of the human immune system remains elusive. Vaccination affects several parameters of the immune system, such as antibody concentration, lymphocyte proliferation and cytokine profiles. This study reviewed reports on vaccination efficiency trials and/or studies in general. Thus the study provides a novel view on the practice of Vaccination has been practiced for hundreds of years, dating back to the 17th century. Throughout history, the mechanisms of vaccination have been studied, refined and improved into what we know vaccination to be today. However, the overall effect of vaccination may have on the homeostasis of the human immune system remains elusive. Vaccination affects several parameters of the immune system, such as antibody concentration, lymphocyte proliferation and cytokine profiles. This study reviewed reports on vaccination efficiency trials and/or studies in general. Vaccination has been practiced for hundreds of years, dating back to the 17th century. Throughout history, the mechanisms of vaccination have been studied, refined and improved into what we know vaccination to be today. However, the overall effect of vaccination may have on the homeostasis of the human immune system remains elusive. Vaccination affects several parameters of the immune system, such as antibody concentration, lymphocyte proliferation and cytokine profiles. This study reviewed reports on vaccination efficiency trials and/or studies in general. Vaccination has been practiced for hundreds of years, dating back to the 17th century. Throughout history, the mechanisms of vaccination have been studied, refined and improved into what we know vaccination to be today. However, the overall effect of vaccination may have on the homeostasis of the human immune system remains elusive. Vaccination affects several parameters of the immune system, such as antibody concentration, lymphocyte proliferation and cytokine profiles. This study reviewed reports on vaccination efficiency trials and/or studies in general. Thus the study provides a novel view on the practice of vaccination and the possible impact it may have on the homeostasis of the immune system. It was observed from the reviewed literature that vaccination can cause an increase in the concentration of total antibody and igG as high as 2.4% and 4.6% respectively. These values are found to be excessive when compared to the minimum protective levels reported which will confer immunity against respective infectious diseases. The high levels of antibodies in circulation may lead to hyperproteinaemia, which may in turn affect blood viscosity, serum sodium, osmolality and the serum osmolar gap. To prevent unwanted post-vaccination adverse effects from happening, a controlled and balanced vaccination practice is required. This balance can be achieved if the immune status of an individual is assessed properly. This also give appropriate emphasis and attention to transfer of maternal antibodies during breastfeeding that helps to minimize the risk of infectious disease and chances of an individual to get infection of a certain infection. Furthermore vaccination program should be designed to mimic natural immune responses to infection.